Altered Brain Penetration of Diclofenac and Mefenamic Acid, but Not Acetaminophen, in Shiga-Like Toxin II-Treated Mice - Masaya Fukuda; Kiyoyuki Kitaichi; Fumie Abe; Yohei Fujimoto; Kenji Takagi; Kenzo Takagi; Tsuneo Morishima; Takaaki Hasegawa (Elsevier, 2005)
It is well accepted that bacterial and virus infections elevate the levels of cytokines in serum and cerebrospinal fluids. Such high levels of cytokines might alter the integrity of the blood-brain barrier (BBB) and/or blood-cerebrospinal fluid barrier (BCSFB), subsequently affecting brain penetration of drugs. However, few reports have addressed this issue. Thus, we investigated brain penetration of cyclooxygenase (COX) inhibitors, commonly used as antipyretics, in mice treated with Shiga-like toxin II (SLT-II) derived from E. coli O157:H7, which significantly elevates cytokine levels. As antipyretics, we used diclofenac, mefenamic acid, and acetaminophen. We found that SLT-II significantly increased the brain-to-plasma concentration ratio (Kp) of diclofenac and mefenamic acid, but not of acetaminophen. Moreover, the Kp of diclofenac and mefenamic acid was increased by probenecid, an anionic compound. These results suggest that efflux anion transporters might be involved in the transport of diclofenac and mefenamic acid. Western blot analysis revealed that SLT-II decreased the expression of organic anion transporter-3, an efflux transporter located on the BBB and/or BCSFB. Taken together, these results suggest that SLT-II and/or SLT-II-stimulated cytokines might change brain penetration of drugs and could possibly increase the risk of their side-effects by altering the expression of transporters. Keywords:: blood-brain barrier, Shiga-like toxin II, organic anion transporter, cyclooxygenase inhibitor